2007
DOI: 10.1021/cg070129l
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Gold Nanoplates: The Case of a Self-Repair Mechanism

Abstract: Figure 4. (a) TEM image of the porous nanoplates with ultra small nanopores shown by the arrows. The inset is the enlarged HRTEM image of nanopore marked "B". (b) Enlarged HRTEM image of the nanopore marked "A" in (a). (c) Nanoplate with a single nanopore left.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Photochemical reduction involves (UV) irradiation of the metal‐precursor solution in the presence of an electron‐donating reagent. UV irradiation has been successfully applied to develop shape‐controlled synthesis of Ag, Au, and Pt nanoparticles 109, 157–164. A more rapid variant of the photochemical method is a mixed chemical–photochemical reduction of metal precursors, where an active reducing agent is also present in reaction solution 165–167.…”
Section: General Strategies For Synthesis Of Nonspherical Nmnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photochemical reduction involves (UV) irradiation of the metal‐precursor solution in the presence of an electron‐donating reagent. UV irradiation has been successfully applied to develop shape‐controlled synthesis of Ag, Au, and Pt nanoparticles 109, 157–164. A more rapid variant of the photochemical method is a mixed chemical–photochemical reduction of metal precursors, where an active reducing agent is also present in reaction solution 165–167.…”
Section: General Strategies For Synthesis Of Nonspherical Nmnpsmentioning
confidence: 99%
“…Yang et al reported an interesting growth mechanism for the formation of nanoplates from spherical gold nanoparticles under continuous UV irradiation 163. The absence of enough protective reagents in the solution and the reduction of electron affinity of gold particles by UV irradiation led to the coalescence of initially formed nanoparticles and the formation of fragments.…”
Section: Mechanisms Of Nonspherical Morphology Evolution In Nmnpsmentioning
confidence: 99%
“…[1][2][3][4] Among the diverse anisotropic Au nanostructures, those characterized with a two-dimensional platelike architecture have been attracting increasing interest and become a hot topic of this eld. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] This is owing to their intrinsic features, such as high aspect ratio, high anisotropy, the existence of fertile sharp corners and edges, etc., [22][23][24][25][26] which endow Au nanoplates with unique optical, electrical, and mechanical properties. These inherent attributes provide Au nanoplates with great opportunities in a wide variety of elds, including but not conned to catalysis, energy conversion, optoelectronics, information storage, sensors, cancer hyperthermia, imaging, surface-enhanced Raman scattering, etc.…”
Section: Introductionmentioning
confidence: 99%
“…It is wellknown that physical, optical, and electronic properties of materials are dependent on their shapes with their sizes reduced to micrometer-or nanometer-scales [6]. So, more efforts have been devoted to the synthesis of one-dimensional (1D) nanotubes, nanowires, and nanorods, and two-dimensional (2D) nanoplates and nanodiscs [7][8][9][10][11]. Now, integration of nanorod/nanowire/ nanoplate as building blocks into hierarchical superstructures was successfully performed [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%